Can you believe it? The effects of benefit type versus construal level on advertisement credibility and purchase intention for organic food. (1st June 2020) - Jäger, Anna-Katharina; Weber, Anja
Abstract: Green marketers are still looking for guidance which advertising appeal will most effectively convince consumers to buy organic food. Extant research mostly investigated the effectiveness of self-/other-benefit appeals and concrete/abstract framing. However, results are contradicting and only few studies examined these factors in combination. Therefore, we explored within an experimental study (representative German sample, n = 297) whether self-benefit appeals (e.g. health advantages) vs. other-benefit appeals (e.g. environmental benefits) or abstract message framing vs. concrete message framing are more effective in generating green purchase intentions. Furthermore, we investigate potential mediators to explore why certain appeals are better suited than others. Results demonstrate that, based on a higher salience of environmental benefit arguments in consumers' minds, other-benefits are more effective in increasing green purchase intentions than self-benefits. Besides, concrete, low construal messages are perceived as more credible than abstractly framed messages, but do not generally increase purchase intentions. The effects of benefit type are completely mediated by message credibility and, to a lower extent, perceived product sustainability and perceived product quality. Our results suggest the use of environmental benefit arguments combined with concrete message framing in advertisement messages for organic food products.